2018
DOI: 10.1038/s41594-018-0171-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcription shapes DNA replication initiation and termination in human cells

Abstract: Although DNA replication is a fundamental aspect of biology, it is not known what determines where DNA replication starts and stops in the human genome. Here we directly identify and quantitatively compare sites of replication initiation and termination in untransformed human cells. We report that replication preferentially initiates at the transcription start site of genes occupied by high levels of RNA polymerase II, and terminates at their polyadenylation sites, thus ensuring global co-directionality of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(185 citation statements)
references
References 44 publications
24
138
0
Order By: Relevance
“…However, there are also substantial differences, as cyclin E overexpression has not been connected to Chk1 inhibitor sensitivity. Recent evidence suggests that transcription and DNA replication initiation sites are closely linked (Chen et al, 2019). We found that cyclin F regulates E2F1 only in the G2/M phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, there are also substantial differences, as cyclin E overexpression has not been connected to Chk1 inhibitor sensitivity. Recent evidence suggests that transcription and DNA replication initiation sites are closely linked (Chen et al, 2019). We found that cyclin F regulates E2F1 only in the G2/M phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 56%
“…It has been shown that cyclin E accumulation leads to reduced DNA replication origin assembly (Ekholm-Reed et al, 2004). Recent evidence suggests that transcription and DNA replication initiation sites are closely linked (Chen et al, 2019). This process predisposes cells to the deleterious consequences of transcription replication collisions and results in the formation of DSBs (Macheret & Halazonetis, 2018).…”
Section: Of 18mentioning
confidence: 99%
“…an association also seen in other eukaryotes (8,10), although the mechanisms might differ. It is unclear how epigenetic dynamics dictate DNA replication activity in L. major.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, with the exception of Saccharomyces and closely related yeasts (3), replication origins in eukaryotes are not defined by conserved sequences. Instead, more elusive features, such as chromatin accessibility, transcription level and epigenetic elements (4)(5)(6)(7)(8)(9)(10), are determinants of replication initiation activity. What is common to all known eukaryotic origins is that they are licensed through binding by the origin recognition complex (ORC), which recruits the replicative helicase, MCM2-7, during G1 (11).…”
Section: Introductionmentioning
confidence: 99%
“…Such a general mechanism may also be relevant to higher eukaryotes. Interestingly, in mammalian cells, replication mainly initiates within gene promoters (Miotto et al 2016;Chen et al 2019). Replication initiation efficiency nicely correlates with transcription initiation strength, which itself correlates with the accessibility of the NDR (Brown et al 2018;Chen et al 2019).…”
Section: A Common Model For All Eukaryotic Ndrs?mentioning
confidence: 99%